Is urban sprawl a threat to sustainable development? a review of characteristics and consequences - Yasin, Muhammad Yazrin; Mohd Yusoff, Mariney; Abdullah, Jamalunlaili; Hj. Mohd. Noor, Norzailawati (Department of Geography, UKM, 2020)
During recent decades, urban sprawl has been substantially debated in the literature, carrying significant social, economic and environment implications, much earlier than of sustainable development concept being introduced. Often, urban sprawl is defined in terms of undesirable development. Urban sprawl is also associated with negative urban expansion and excessive resource consumption. To mitigate urban sprawl, urban growth management has been timely implemented by understanding urbanization characteristics and their socio-environment and economic driving forces. While sustainable urban development is a highly developed spatial form of integrated cities, urban sprawl mostly occurred in lower densities accompanied by expansion of urban periphery, is acknowledged as the opposite force, with its character of scattered and leapfrogging development. Therefore, urban sprawl is the most impactful urban development patterns that occurred at an unprecedented rate that threaten sustainable development. This article examined the characteristics and the consequences of urban sprawl and how it affects sustainable development.